Pengaruh Rasio Keuangan Terhadap Nilai Perusahaan pada Perusahaan Sektor Otomotif yang Terdaftar di Bursa Efek Indonesia Periode 2019–2023 - Heri Sastra; A. Taufik Nur Saleh; Rini Syarif (Jurnal Aplikasi Bisnis Kesatuan, 2026)
Price to book value is an indicator that investors consider before making an investment, and many investors see good companies as having a high price to book value. The purpose of this research is to test and determine whether there is an influence of the current ratio, debt to asset ratio, return on equity, and total asset turnover on the price to book value of automotive companies listed on the Indonesia Stock Exchange for the period 2019-2023. This study consists of 10 companies selected using the purposive sampling technique from 20 companies in the automotive sector over a 5-year period. The data testing method in this study uses classical assumption tests, and for the data analysis method, it uses panel data regression analysis with the help of the E-Views 13 application. The results of this study show that the current ratio has no effect on the price to book value, the debt to asset ratio has no effect on the price to book value, return on equity has a positive effect on the price to book value, and total asset turnover has no effect on the price to book value.While the current ratio, debt to asset ratio, return on equity, and total asset turnover together have no effect on price to book value. Keywords: Current Ratio, Debt to Asset Ratio, Return on Equity, Total Aset Turnover, Price to Book Value.